STUDENTS’ PERCEPTIONS OF QUR’AN AND HADITH LEARNING AND INSTRUCTIONAL IMPLEMENTATION - Zulham Luthfi Tambunan; Nurlaili (LPPM Universitas PGRI Pontianak, 2025)
Students’ perceptions of Qur’an and Hadith learning play a crucial role in determining instructional effectiveness within Integrated Islamic Schools (SIT), as they reflect students’ engagement, understanding, and internalization of Islamic values. This study examines the effects of lesson planning (X1) and lesson implementation (X2) on students’ perceptions of the effectiveness of Qur’an and Hadith learning (Y). Employing a mixed-methods design, data were collected from 53 students through Likert-scale questionnaires and from three Islamic Education teachers through semi-structured interviews. Regression analysis indicates that lesson implementation (X2) has a significant effect on students’ perceptions (p = 0.000; r = 0.647), whereas lesson planning (X1) shows no significant effect (p = 0.092), suggesting that well-designed plans are not always translated into engaging classroom practices. The regression model (R² = 0.450) explains 45% of the variance in students’ perceptions. This study highlights students’ perceptions as a critical evaluative indicator and underscores the need for creative, interactive, and technology-supported instructional strategies in Qur’an and Hadith learning.